Revitalization of Islamic Education as a Strategy for Shaping an Adaptive Qur'anic Generation in the VUCA Era - Razak, Abdul (Fast in Social Sciences, 2025)
This article explores the revitalization of Islamic education in the context of the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era, emphasizing its critical role in shaping an adaptive, Qur'anic generation. As the world faces rapid changes and challenges, it is crucial for Islamic education to evolve and remain relevant, balancing intellectual knowledge with the development of strong moral and spiritual character. This study highlights the importance of integrating Qur'anic values into the curriculum to produce individuals who are not only academically proficient but also morally grounded, capable of navigating a dynamic global environment. Additionally, the paper discusses the significant role of technology in enhancing Islamic education by expanding access to learning and fostering interactive, flexible educational experiences. The research utilizes a qualitative descriptive method with a literature review approach, analyzing various sources to identify patterns and strategies for strengthening Islamic education. The findings suggest that revitalizing the Islamic education curriculum to integrate Qur'anic values and technological tools is essential for preparing youth to meet global challenges while preserving their Islamic identity and ethical principles. This study offers insights into how Islamic education can adapt to the modern world, ensuring that future generations are not only knowledgeable but also ethical, responsible, and equipped to contribute positively to society.